Active role of flower shops in the commercialization of roses - Nereida Rodríguez Orozco; Emmanuel Vázquez Anastasio; Ariadna Linares Gabriel; Mario Alejandro Hernández Chontal (Ornamental Horticulture, 2021)
Retail florist activities are essential elements in the rose (Rosa spp.) market since they generate significant income and employment. In these jobs, florists gain recognition by their designs that captivate consumers. At the same time, they are key entrepreneurs in the commercialization of roses. Then, the objective of the research was to know the entrepreneurial role of florists in the commercialization of roses (Rosa spp.) in southern Veracruz, Mexico. An exploratory research was conducted in flower shops, five in Coatzacoalcos, nine in Minatitlán and six in Acayucan. Interviews were conducted with florists (n = 20). The categories of analysis used were the demographic, psychosocial and sociocultural profile of the florists as innovative entrepreneurs. In regards to the demographic profile, these economic agents have the experience and knowledge necessary to develop their activity. In short, florists are identified as family micro-enterprises with establishments that are 20 years old. In the psychosocial profile, florists present low innovative capacity with respect to the composition of their floral arrangements; however, they are characterized as risk takers with the ability to solve problems. Finally, the sociocultural profile demonstrates the florists-intermediary-producers collaboration; such entrepreneurial activity generates economic incentives with local-regional influence. Therefore, florists need to strengthen their links with other florists, producers and distributors to improve their innovative capabilities that will benefit both themselves and consumers.